Pragmatic circuits : signals and filters - Eccles, William J. (Synthesis lectures on digital circuits and systems ;, 2006)
Pragmatic Circuits: Signals and Filters is built around the processing of signals. Topics include spectra, a short introduction to the Fourier series, design of filters, and the properties of the Fourier transform. The focus is on signals rather than power. But the treatment is still pragmatic. For example, the author accepts the work of Butterworth and uses his results to design filters in a fairly methodical fashion. This third of three volumes finishes with a look at spectra by showing how to get a spectrum even if a signal is not periodic. The Fourier transform provides a way of dealing with such non-periodic signals. The two other volumes in the Pragmatic Circuits series include titles on DC and Time Domain and Frequency Domain. These short lecture books will be of use to students at any level of electrical engineering and for practicing engineers, or scientists, in any field looking for a practical and applied introduction to circuits and signals. The author's "pragmatic" and applied style gives a unique and helpful "non-idealistic, practical, opinionated" introduction to circuits.